The Effect of Clean and Healthy Life Behaviors (PHBS) on Diarrhea Incidence - Hikma Rafiah Nadjib; Windhu Purnomo; Rachmah Indawati (Health Notions, 2018)
Diarrhea is the second disease that causes death in infants (children) under five years). Data and Information Indonesia Health Profile 2016, the number of diarrhea cases in Indonesia is 2,544,084 people or equivalent to 36.9% of the total incidence of diarrhea in 2016. South Central Timor District is the second area with the largest frequency distribution of outbreaks in Indonesia after Central Sulawesi (Depkes, 2011). The purpose of this study was to analyze the effect of PHBS households to diarrhea incidence in Southern Timor in 2016. The type of research used was observational analytic research with cross sectional study approach. The sample in this research was taken using simple random sampling technique with sample size 29 health centers. There is influence of variable percentage of PHBS households to diarrhea incidence in Southern Timor District. Nila R equal to 0,423 means closeness relation between independent variable with dependent variable is equal to 0423 (medium). Diarrhea rate was formulated with 23,884 minus multiplication of 0.174 with percentage of household with PHBS. The need for improved services outside the health center building for the discovery of diarrhea cases and the need for promotive and preventive efforts against the growing factors of diarrhea occurrence in South Central Timor District.Keywords: PHBS, Households, Diarrhea